Impact of Meteorological Parameters on Solar Radiation over Langtang National Park, Nepal - Shrestha, Prakash M.; Gupta, Suresh P.; Joshi, Usha; Chapagain, Narayan P.; Karki, Indra B.; Poudyal, Khem N. (Patan Pragya, 2023)
The main objective of this research is to study the impact of meteorological parameters on atmospheric turbidity index on Langtang National Park (28.2112° N, 85.5663° E, 3862 m asl) for a period of one year (2018). Daily data of Aerosol optical depth (AOD) and meteorological parameters are obtained from AERONET and NASA website respectively. The maximum and minimum values of direct solar radiation (IB) during the study period are found 1286 ± 24 W/m2 in January and 1123 ± 3 W/m2 in August respectively. The maximum and minimum value of diffuse solar radiation (ID) is found 119 ± 21 W/m2 in April and 59 ± 2 W/m2 in August respectively. The annual average of direct solar radiation and diffuse solar radiation are found 1202 ± 63 W/m2 and 90 ± 20 W/m2 respectively. There is a negative effect of maximum temperature, minimum temperature, dew point, relative humidity, water contend and rainfall on IB, but no significant effect of those parameters on ID. The result of this research work is beneficial for the further identification, impact and analysis of solar radiation at different places with same geographical and meteorological condition. The study of solar radiation is important for energy harvesting and agriculture.